Desarrollo de los modelos estático y dinámico del yacimiento mediante simulación numérica para la formación carbonera C7 del campo ubicado en el bloque Río Meta – Cuenca de los Llanos Orientales (2016)
This degree project presents the development of static and dynamic models for Carbonera C7 formation of the field located in the Meta River Block -Basin of the Eastern Plains by numerical simulation; for this the company program PEOffice Optimization Petroleum Technologies and Schlumberger Petrel was used. The static reservoir model was performed by the characterization of the fluids in the reservoir, petrophysical review of the information provided by the operating company and the geological modeling of the field.